Knowledge about Preeclampsia among Women of Reproductive Age Attending Al-Beyda Medical Center - Faiza Taher; Marfoua Ali; Ghada Otman (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The objective of the present study was to assess the knowledge of preeclampsia and it is dangerous signs and maternal and fetal complications, among women of reproductive age attending Albeyda Medical Center. Method. A descriptive cross sectional study was performed at Albeyda Medical Center in the east region in Libya. Data was collected by distributing a questionnaire on women at reproductive age attended gynecological and obstetric department from 15 January until 15 December 2021. Results. About 299 participants agreed to answer the questionnaire. Preeclampsia was unknown by more than half of the participants (54.90 percent). More than half (53.5%) of participant had no local name of pre-eclampsia in the area, and just 3.7% of people knew the name. According to the results, excessive salt consumption was the major cause of high blood pressure during pregnancy and follow by stress (23.4% and 12.4% respectively). Headache, dizziness, odema, and convulsion were the most well-known signs danger of preeclampsia according to those who responded, and they account for 73.3%, 69.6%, 66.9% and 61.9% respectively. Regarding the maternal complications of preeclampsia, maternal death and cesarean section were the most known and frequent maternal complication, while fetal complications, Prematurity, IUGR the occurrence of fetal death in utero were the best known and account for 43.1% and 21.7% respectively. To prevent preeclampsia, about 37.1%, 13.4% believed that reducing salt consumption taking low dose of aspirin would reduce the incidence of preeclampsia respectively. Conclusion. Knowledge of preeclampsia, its significant signs, and maternal and fetal complications among pregnant women in the study area is low. Lack of formal education and not attending four or more antenatal care visits were associated with poor knowledge of preeclampsia. Education of pregnant women on the signs and risks of this disease must be carried out systematically by health workers during antinatal care.